2019
DOI: 10.1055/s-0038-1677472
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal IGF-1 and IGFBP-1 Blood Levels in Extremely Preterm Infants: Relationships with Indicators of Placental Insufficiency and with Systemic Inflammation

Abstract: Objective To evaluate to what extent indicators of placenta insufficiency are associated with low concentrations of insulin-like growth factor 1 (IGF-1) and IGF-1–binding protein-1 (IGFBP-1) in neonatal blood, and to what extent the concentrations of these growth factors are associated with concentrations of proteins with inflammatory, neurotrophic, or angiogenic properties. Study Design Using multiplex immunoassays, we measured the concentrations of IGF-1 and IGFBP-1, as well as 25 other proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 82 publications
0
10
0
1
Order By: Relevance
“…Insulin binding proteins are highly expressed by the fetus and in the decidua basalis, and are key regulators of the bioavailability of insulin-like growth factor-1 (IGF-1) and hence fetal growth. For instance, IGFBP1 is associated with intrauterine growth restriction and impaired placentation, and is raised in cord blood from extremely preterm infants, 33 whereas IGFBP2 has also been found to be up-regulated in whole blood RNA before PPROM. 34 The detection of IGFBP cfRNA, as a predominant signal in pregnancies that result in very early sPTB is both plausible and potentially informative in terms of downstream events.…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…Insulin binding proteins are highly expressed by the fetus and in the decidua basalis, and are key regulators of the bioavailability of insulin-like growth factor-1 (IGF-1) and hence fetal growth. For instance, IGFBP1 is associated with intrauterine growth restriction and impaired placentation, and is raised in cord blood from extremely preterm infants, 33 whereas IGFBP2 has also been found to be up-regulated in whole blood RNA before PPROM. 34 The detection of IGFBP cfRNA, as a predominant signal in pregnancies that result in very early sPTB is both plausible and potentially informative in terms of downstream events.…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…Previous studies have shown that the pathological mechanisms of executive dysfunction may be involved in immunoinflammatory alterations and dysregulated redox balance. For example, high concentrations of IL-8 were previously found to be related to executive dysfunctions in SCZ, children born at very early birth, and patients with chronic low back pain (18,70–72). Elevated MDA and decreased SOD have also been shown to be associated with executive dysfunctions in various diseases and healthy individuals (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…98 Sex differences in outcome of fetuses with FGR might result from sex-specific changes in the structure and function of the placenta in response to processes that underlie FGR. 104 Fetal growth restriction and inflammation-related proteins Potential molecular mechanisms that might underlie associations between fetal growth restriction and BPD, NEC, and cerebral white matter include insufficiency of growth factors, such as insulin-like growth factor-1, and neurotrophic factors, such as neurotrophin-4 and brain-derived neurotrophic factor, 105,106 as well as increased expression, during the first postnatal month, of inflammatory proteins in neonatal blood, including cytokines (IL-1β, IL-6, TNF-α, and IL-8), chemokines (monocyte chemoattractant protein-4), adhesion molecules (E-selectin and intracellular adhesion molecule-1 and -3), and matrix metalloproteinase-9. 31 Although ELGAN Study infants with FGR, as well as those born to mothers with preeclampsia, were less likely than infants without FGR to have systemic inflammation on the first postnatal day, they were more likely to have systemic inflammation in the second week of life.…”
Section: Mechanism 2: Disrupted Placental Programming and Neurodevelomentioning
confidence: 99%